Perlindungan Hak Ahli Waris terhadap Aset Digital di Indonesia - Heriyanto Heriyanto; Yulius Efendi; Teguh Wicaksono (Lembaga Pengembangan Kinerja Dosen, 2024)
The protection of heirs' rights to digital assets in Indonesia is becoming increasingly important as digital technology usage grows. Digital assets, including social media accounts, emails, digital files, and cryptocurrencies, present new challenges in inheritance law due to their unique nature. This article discusses how heirs' rights to digital assets can be effectively regulated within the existing legal framework. The main challenges include access and control issues, an incomplete legal framework, and rapid technological advancements. Proposed solutions include updating legal regulations, collaborating with digital service providers, enhancing digital literacy, and developing supportive systems and services. With these measures, it is hoped that heirs' rights to digital assets can be well-protected, providing legal certainty and ensuring that digital assets are not lost or misused.